Over-prescribing of antibiotics and imaging in the management of uncomplicated URIs in emergency departments - Xu, K Tom (BioMed Central, 2013)
BACKGROUND: Unnecessary use of resources for common illnesses has substantial effect on patient care and costs. Evidence-based guidelines do not recommend antibiotics or imaging for uncomplicated upper respiratory infections (URIs). The objective of the current study was to examine medical care providers’ compliance with guidelines in treating uncomplicated URIs in emergency departments (EDs) in the US. METHODS: Nationally representative data from the NHAMCS 2007 and 2008 were used. Uncomplicated URIs were identified through ICD-9 codes of nasopharyngitis, laryngitis, bronchitis, URI not otherwise specified and influenza involving upper respiratory tract. Exclusion criteria were concurrent comorbidities, follow-up visits, and age < 18 or >64 years. Most frequently prescribed classes of antibiotics were identified. Multivariate analyses were conducted to identify the factors associated with the prescribing of antibiotics and use of imaging studies. RESULTS: In 2007 and 2008, there were 2.2 million adult uncomplicated URI visits without any other concurrent diagnoses in EDs in the US. Approximately 52% were given antibiotic prescriptions, over one-third of which were macrolides, and nearly half of the visits performed imaging studies. About 51% had a diagnosis of bronchitis, 35% URI NOS, 9% nasopharyngitis, laryngitis or influenza, and 4% multiple URI diagnoses. The diagnosis of bronchitis, fever at presentation, older ages, male gender, longer waiting time, and metropolitan areas were associated with a greater likelihood of prescribing antibiotics or imaging studies, controlling for confounding factors. CONCLUSION: Despite the recommendations and campaign efforts by the CDC and many medical associations, the prescribing of antibiotics in treating uncomplicated URIs in the EDs remains prevalent. Furthermore, overutilization of imaging studies is prevalent. Changes at levels of health care system and hospitals are needed to avoid unnecessary resource utilization. In addition, further patient education about antibiotic use in the community may greatly facilitate the transition out of an antibiotic-dependent consumer culture.